2017
DOI: 10.1007/s13753-017-0115-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Temperature-Related Weather Index for Agricultural Insurance of Three Main Crops in China

Abstract: In this study, two categories of weather indexabsolute index and relative index-for chilling injury and heat damage of three main crops in China were assessed to identify insurable counties. First, correlations between selected weather indices and yield losses were examined for each county. If a correlation was significant, the county was categorized as ''insurable'' for the corresponding hazard or index. Second, the spatial distribution of insurable counties was characterized and finally, their correlation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This result was consistent with the conclusion that climate data can achieve much better predictive performance than satellite data (Cai et al 2019) due to its direct impacts on yield. Tao et al (2008) found that major crop yields were significantly related to growing season climate (precipitation, temperature) and Zhang et al (2017) believed that climatic variables are key controls on crop growth and determining yields. The temperature increase during the grain-filling stage can easily shorten the filling time, which affects the formation of yield (Siebert et al 2017;Zampieri et al 2017).…”
Section: The Importance Of Forcing Data Type In Yield Estimationmentioning
confidence: 99%
“…This result was consistent with the conclusion that climate data can achieve much better predictive performance than satellite data (Cai et al 2019) due to its direct impacts on yield. Tao et al (2008) found that major crop yields were significantly related to growing season climate (precipitation, temperature) and Zhang et al (2017) believed that climatic variables are key controls on crop growth and determining yields. The temperature increase during the grain-filling stage can easily shorten the filling time, which affects the formation of yield (Siebert et al 2017;Zampieri et al 2017).…”
Section: The Importance Of Forcing Data Type In Yield Estimationmentioning
confidence: 99%
“…The average weather conditions that occur with wide area coverage, long time, topography which is influenced by the distance from the sun to the earth. The position of the sun towards the earth also causes climate differences, the area around the equator has a tropical climate, the area between 23.5 o C to 66.5 o C north latitude and south latitude has a subtropical climate, the rest has a polar climate (Riaman et al, 2022b), (Zhang et al, 2017).…”
Section: A Introductionmentioning
confidence: 99%
“…Farmers can transfer these risks to other parties to overcome losses. One of them is through the paddy agricultural insurance program which is one of the Ministry of Agriculture's programs [4,5]. A lot of research on agricultural insurance has been undertaken, as indicated by various publications that have been published.…”
Section: Introductionmentioning
confidence: 99%